The bone season - Shannon, Samantha, 1991- (Shannon, Samantha, 1991- Bone season., 2013)
In the mid-21st century major world cities are controlled by a formidable security force and clairvoyant underworld cell member Paige commits acts of psychic treason before being captured by an otherworldly race that would make her a part of their supernatural army.